Confucius on Leadership - Adair, John. (Oxford Macmillan, 2013)
Few things are more important than the quality and credibility of leaders, as they play a vital role in every aspect of our modern lives. Yet strong leadership is a difficult skill to master. Good leaders must learn not only to manage, analyse and appraise, but also to encourage, improve and inspire. Here, John Adair, the celebrated expert on leadership training, shows how Confucian philosophy can help you become a better leader. He demonstrates how, far from merely being interesting ideas from centuries ago, Confucius's sayings, or Analects, will help you to develop the confidence, characteristics and skills you need to be the best leader you can be.
Includes index
Keywords: Leadership